Esensi Lesson Study di Era 4.0 - Dianna Ratnawati (Department of Mechanical Engineering Education, 2019)
Collaborative and sustainable actions carried out by a group of teachers/lecturers through lesson study with an information and communication technologies approach can meet the needs of the world of education in era 4.0. This study aims to analyze the impact of the application of lesson study in learning activities on the technical measurement on mechanical engineering students of the Universitas Sarjanawiyata Tamansiswa. The research method uses lesson research with a qualitative approach. The applied lesson study model adopts Saito et al. (2005), in which its implementation consists of 2 cycles, each cycle includes the stages of the plan, do, and see. The learning media used are a digital book, e-learning using Edmodo, Toyota 7k engine stand, handphone, cylinder block, clutch, differential, dial gauge, cylinder gauge, vernier caliper, and micrometer. The sample selected amounted to 30 students and involved two observers in each cycle. The results of this study indicate that the essence of lesson study has an impact on increasing student activity by 40% in cycle 1 and 34% in cycle 2. The lesson study also has an effect on improving the quality of the lecturer's evaluation on the students' learning outcomesTindakan kolaboratif dan berkelanjutan yang dilakukan sekelompok guru/dosen melalui lesson study dengan pendekatan information and communication technologies dapat memenuhi kebutuhan dunia pendidikan di era 4.0. Penelitian ini bertujuan untuk menganalisis dampak penerapan lesson study dalam kegiatan pembelajaran pengukuran teknik pada mahasiswa pendidikan teknik mesin Universitas Sarjanawiyata Tamansiswa. Metode penelitian menggunakan lesson research dengan pendekatan kualitatif. Model lesson study yang diterapkan mengadopsi dari Saito dkk (2005), dimana dalam pelaksanaannya terdiri dari 2 siklus dengan tahapan tiap siklusnya meliputi plan, do, dan see. Media pembelajaran yang digunakan adalah digital book, e-learning melalui edmodo, engine stand toyota 7k, handphone, blok silinder, kopling, gardan, dial gauge, cylinder gauge vernier celiper dan mikrometer. Sampel yang dipilih berjumlah 30 mahasiswa dengan melibatkan 2 observer pada tiap siklusnya. Hasil penelitian ini menunjukkan bahwa esensi lesson study berdampak pada peningkatan keaktifan siswa sebesar 40% pada siklus 1 dan meningkat 34% pada siklus 2, selain itu berdampak pada peningkatan kualitas evaluasi dosen terhadap hasil belajar mahasiswa